On separation axioms in intuitionistic topological spaces - Sadik Bayhan; Doğan Çoker (International Journal of Mathematics and Mathematical Sciences)
The purpose of this paper is to investigate several types of separation axioms in intuitionistic topological spaces, developed by Çoker (2000). After giving some characterizations of T1 and T2 separation axioms in intuitionistic topological spaces, we give interrelations between several types of separation axioms and some counterexamples.